Międzykulturowe problemy kadry menedżerskiej w Polsce - Stor, Marzena (Cross-cultural issues within managerial staff relations in Poland, 2006)
The literature review provides a wide range of multidimensional models that are used to describe cross-cultural differences at national level. But applying them to deal with particular organizational problems is often limited as in most cases they employ relatively high level of generality and simplification and do not take a dynamic view on sociocultural changes of societies. This is why the author of the present article focuses on some alternative approach to cross-cultural research at organizational level. First the CIS method is presented and then some data collected by this method in 32 international organizations in Poland are discussed. The main conclusion is that basing on early categorization of national differences in multinational relations within the managerial staff is dangerous to these relations, threatening their trouble free run. Consequently, this proves that involving cross-cultural models, that are well-settled in the literature, to cope with situational problems, may sometimes only enhance stereotypization and lead to more serious conflict instead.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 423-437